Reconfiguring knowledge management: Combining intellectual capital, intangible assets and knowledge creation - Tomi Hussi (The Research Institute of the Finnish Economy (ETLA), 2003)
Intellectual Capital, Intangible Assets and Knowledge Creation are all concepts that are strongly linked to the phenomenon of Knowledge Management. Yet they have only been parallel to each other. This controversy between different approaches has also resulted in vague definitions of Knowledge Management. This paper will critically discuss the definitions of these concepts. The analysis shows that different concepts actually focus on different angles of the topic. Based on this, a model will be built that ties all of them into a unitary entity. At the same time, this model gives a reconfigured definition of the concept of knowledge management. – – Osaamispääoma, aineeton varallisuus ja tiedonluominen ovat tietämyksen johtamisen elementtejä. Näiden käsitteiden välisistä kytköksistä tiedetään kuitenkin liian vähän. Käsitteiden kirjo on osaltaan vaikeuttanut tietämyksen johtamisen selkeää määrittelemistä. Käsitemäärittelyjen tarkastelu osoittaa, että yrityksen arvon luomiseen liittyvät eri käsitteet painotukset poikkeavat toisistaan. Erilaisten näkökulmien suhteuttaminen toisiinsa tuottaa uudenlaisen käsitteellisen järjestelmän, joka määrittelee myös tietämyksen johtamisen uudenlaisella tavalla. – osaamispääoma ; arvoa synnyttävä aineeton varallisuus ; kaupallisesti hyödynnettävissä oleva aineeton varallisuus ; tiedonluominen ; tietämyksen johtaminen
Keywords: 330; intellectual capital; intangible assets; generative intangibles; commercially exploitable intangibles; knowledge creation; knowledge management; Intangibles Gut; Wissensmanagement